Building A Tax System for Hydrocarbon Industry: Study Case for Romania - Cornelia NEAGU; Dr. Marius BULEARCĂ; Dr. Marius BULEARCĂ; Cristian SIMA; Daniel FISTUNG (Communications of International Proceedings, 2025)
Establishing an appropriate oil and gas sector taxation regime for Romania must start with analyzing the specific elements of a tax system in the hydrocarbon industry. In doing this, in the beggining the article highlights the main elements characterizing a tax system specific to the hydrocarbon extraction sector, focussing on the three main types of legal arrangements. Next, the paper analyzes the premises for establishing an optimal fiscal system for production of hydrocarbons, such as the physical and technical conditions, and development prognosis of the industry. The remainig of the paper proposes the main elements that may be the basis of an adequate tax system for Romania, starting from analyzing the specific conditions of this sector.
Keywords: oil; natural gas; European Union; royalty; taxation; concession; income